Beetles species richness along environmental gradients at montane ecosystem in Fraser’s Hill, Peninsular Malaysia - Muneeb M. Musthafa,; Fauziah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study measures beetle diversity and distribution pattern along elevations at Fraser’s Hill, a pristine tropical forest in Malaysia. Sites were sampled at 500 m, 1000 m, 1500 m and 1800 m a.s.l. using two light traps, two Malaise traps and 25 pitfall traps at each elevation. Sampling was carried out at three months’ intervals in 2015. Altogether, 1981 beetles representing 32 families and 116 species were collected, with proportion of obtained species above 70% at all elevations. Species richness was not significant among elevations, thus forming no discernible pattern of species distribution. Higher Shannon diversity increased steadily with elevation and dominance was lowest at the two highest elevations, while beetle abundance decreases significantly with elevation. There was no significant difference between the diversity values at 500 m and 1000 m, and 1500 m and 1800 m, whereas there was significant difference between 500 m and 1500 m, and 1000 m and 1800 m. The results highlight the importance of different microhabitats for different beetle species and their own responses to environmental parameters that differ with altitudinal clines. These findings also highlight the importance of Fraser’s Hill as a key location for biological conservation and as protected area.